UPAYA ANAK JALANAN DALAM MEMPEROLEH PENDIDIKAN ISLAM - Setyaningrum, Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2017)
This study explains efforts for street children to obtain Islamic Education. Islam as a way of life gives a thorough attention to the growth and development of children physical and psychological aspects. The problem is, the majority of street children are neglected in the field of education because of dropping out of school in the productive age. The existence and activation of Islamic boarding schools, NGOs, and even educational volunteers have not been maximized. One sample, according to Social Rehabilitation Section Data, Malang City Social Service, total number of children in 2014 is still 548 children.This study is a type of library research, through qualitative descriptive approach with data collection method of documentation study. Specifically, according to the results of the study, humanist, dialogical, reflective, expressive, and basic needs fulfillment approach is suitable. The form of modeling (“uswatun khasanah”) with parenting pattern can give impact. This research suggestion, Islamic education can be done through formal form, nonformal, and informal. Pondok Pesantren, shelter houses, and mosques can be a means, including cooperation among Non Government Associations (NGO's). At the end of the analysis, the researcher suggests that there is early psychological diagnosis and procurement of exclusive kiddos/kindergartens.